Social orienting in prematurely born preschoolers: a case control study showing altered neural tuning towards voices, not faces - Rowena Van den Broeck; Lisa Gistelinck; Sofie Vettori; Ward Deferm; Silke Vos; Bieke Bollen; Gunnar Naulaers; Els Ortibus; Bart Boets (Molecular Autism)
Abstract Background Despite advancements in neonatal care, premature infants remain at increased risk for cognitive and socio-emotional difficulties, collectively referred to as the preterm behavioral phenotype. A particular aspect of this phenotype is atypical social orienting, characterized by reduced attention towards socially relevant information, similar to what has been reported for autism spectrum disorder. Methods We monitored a cohort of prematurely born children from birth. At five years of age, we administered a series of frequency-tagging electroencephalography (EEG) paradigms to investigate their neural sensitivity to social cues, i.e., sensitivity for faces and voices. Frequency-tagging EEG utilizes fast periodic stimulation to elicit synchronized brain responses measurable in the frequency domain. In the preterm (N = 66) and in a matched full-term control group (N = 32), we applied two multi-input frequency-tagging EEG paradigms, simultaneously presenting streams of social and non-social stimuli, each tagged at different presentation rates. In the visual domain, we presented streams of faces and houses. In the auditory domain, we presented streams of voices and object sounds. We used linear mixed models to investigate the effects of group and stimulus type. Results All children showed an implicit social bias towards faces and voices. Compared to full-term peers, preterm preschoolers showed intact neural tuning to faces, but diminished neural tuning to voices, in particular in the speech-sensitive 3.70 Hz frequency band. Limitations The preterm group was highly heterogeneous in terms of gestational age and consisted of healthy preterm preschoolers. Moreover, the used paradigms are artificial and may not fully capture neural tuning in naturalistic social interactions. Conclusions The diminished neural response to voices in the preterm children may potentially reflect the effects of atypical auditory exposure and premature visual exposure in the NICU environment or altered social experiences early in life. These findings contribute to our understanding of the socio-emotional and communicative development in preterm populations and may aid in identifying children at risk for psychopathology or subclinical socio-emotional difficulties.